2018
DOI: 10.3390/ph11010003
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antibiofilm Activity of UP-5, an Ultrashort Antimicrobial Peptide Designed Using Only Arginine and Biphenylalanine

Abstract: The recent upsurge of multidrug resistant bacteria (MDRB) among global communities has become one of the most serious challenges facing health professionals and the human population worldwide. Cationic ultrashort antimicrobial peptides (USAMPs) are a promising group of molecules that meet the required criteria of novel antimicrobial drug development. UP-5, a novel penta-peptide, displayed significant antimicrobial activities against various standard and clinical isolates of MDRB. UP-5 displayed MICs values wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 71 publications
(80 reference statements)
1
34
0
Order By: Relevance
“…Many natural AMPs are in the range of 10 to 50 amino acids in length. The length of AMPs directly translates into production cost of AMPs in the development stage; hence, the discovery of ultrashort and/or truncated AMPs with less than five amino acids has been pursued . For instance, a synthetic tripeptide LTX‐109 ( 17 , Figure ) is derived from bovine lactoferricin, which corresponds to 17 to 31 lactoferrin fragment, FKCRRWQWRMKKLGA.…”
Section: Improvement Strategies Of Ampsmentioning
confidence: 99%
“…Many natural AMPs are in the range of 10 to 50 amino acids in length. The length of AMPs directly translates into production cost of AMPs in the development stage; hence, the discovery of ultrashort and/or truncated AMPs with less than five amino acids has been pursued . For instance, a synthetic tripeptide LTX‐109 ( 17 , Figure ) is derived from bovine lactoferricin, which corresponds to 17 to 31 lactoferrin fragment, FKCRRWQWRMKKLGA.…”
Section: Improvement Strategies Of Ampsmentioning
confidence: 99%
“…Accordingly, there are many possible modifications ranging from the incorporation of unnatural amino acids (of which more than 700 are known [36]) and peptides with altered backbones, to entirely different chemical structures. These modifications and structural differences are often able to resolve stability and cytotoxicity issues [30,32,35]. Raman et al [30], for example, designed a β-peptide with anti-fungal and anti-biofilm activity against Candida albicans, which remained structurally stable and active in synthetic urine media.…”
Section: Design Of Anti-biofilm Peptidesmentioning
confidence: 99%
“…Raman et al [30], for example, designed a β-peptide with anti-fungal and anti-biofilm activity against Candida albicans, which remained structurally stable and active in synthetic urine media. A peptidomimetic of 5 residues containing only arginine and biphenylalanine also showed anti-biofilm activity against multiple Gram-negative and Gram-positive bacteria, and exhibited very low toxicity to human erythrocytes and Vero monkey kidney epithelial cells, purportedly due to its short size and low hydrophobicity [32]. Conversely one study showed that enantiomeric peptides with D amino acids tended to have potent activity while being protease resistant [16,17].…”
Section: Design Of Anti-biofilm Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpretation and assessment of the FIC indices were performed according to the broth microdilution checkerboard technique. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%